Greening transportation and parking at University of Coimbra - Cruz, Luís (2017)
This article explores the potential contribution of integrated traffic and parking management strategies to ensure more rational use of available parking spaces, and to reduce fuel consumption and greenhouse gas (GHG) emissions by commuters traveling to the University of Coimbra main campus. An integrated modelling approach is used, including the characterization of supply and demand for parking and public transport, the creation and implementation of a survey to campus users, and a life-cycle approach to assess six transportation and parking strategy scenarios. This comprehensive analysis demonstrates the importance of integrated management measures to greening commuters’ transportation and parking within a University campus, identifying and quantifying opportunities for successfully making the transitions towards a more sustainable future, namely increasing well-being and reducing environmental impact. Results demonstrate that effective control of illegal parking and different forms of modal shift towards public transportation may contribute to important reductions in environmental impacts. Local population reveals willingness to participate in collective efforts to tackle traffic and parking problems, challenging authorities to take action and empowering ever more people to engage in such cathartic changes. This comprehensive approach is highly valuable for the management of parking and traffic within university campuses, providing innovative lessons on the social and environmental impacts that would result from this policy approach to urban areas (e.g. historical centers) facing the typical problems of a carbon society, such as traffic congestion, non-regulated parking and intensive car use.